AKTIFITAS FISIK, POLA MAKAN DAN VARIASI KERJA UNTUK PENCEGAHAN DIABETES MELITUS - Santy Siregar; Mafe Robbi Simanjuntak; Ulina Karo-karo (Jurnal Maternitas Kebidanan, 2022)
Office workers generally have low physical activity, causing a lack of burning energy by the body. Energy in the body will be stored in fat and cause the amount of fat deposits in the body is not reduced as well as an increase in glucose in the blood. Eventually workers experience an increase in weight and blood sugar levels. Lifestyle like this is at risk for diabetes mellitus. Efforts in controlling blood sugar levels (KGD) are not effective only done with treatment, therefore for prevention as early as possible it needs to be done through physical activity, dietary arrangements and varied work patterns. This literature study uses the Literature Review Comparative Study method, with secondary data of online journals through trusted websites / websites using the application publish of perish with keywords prevention, diabetes mellitus, diet, productive age, activity. In this literature study there are 13 journals reviewed on how prevention, treatment and methods used to find out diabetes mellitus for workers at productive age. From 13 studies that riview obtained that physical activity, streching, aerobic exercise and diabetic foot gymnastics are able to lower glucose levels in the blood. Diabetic gymnastics is effective in lowering blood glucose levels. Diabetic exercise has benefits in controlling blood sugar, and risk factors for cardiovascular disease. By doing gymnastics consistently the need for oral medication and insulin is reduced. For diet, it is obtained that purple-line yam cookies with low carbohydrates and fiber can be an alternative snack for diabetic mellitus.